2014
DOI: 10.1097/mcc.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation in adult patients with acute respiratory distress syndrome

Abstract: Purpose of the reviewExamine the role of ECMO as potential therapeutic option for severe cases of ARDS. Recent findingsUse of ECMO to treat acute respiratory failure dramatically increased. addresses clinicians to the best treatment options in respect of the severity of illness and allocate ECMO as a potential therapeutic option for patients with severe ARDS and a P/F ration lower than 100 and proposed that the indication of ECMO may be shifted from the treatment of choice for refractory hypoxemia to the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 26 publications
0
23
0
2
Order By: Relevance
“…These early studies showed improved mortality in models of lidocaine and amitriptyline poisoning [11,12]. Numerous human case reports and case series have since shown favorable outcomes although ECMO has been primarily used in poisonings involving pharmaceuticals such as antidysrhythmics and other cardiovascular medications, as well as tricyclic antidepressants [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…These early studies showed improved mortality in models of lidocaine and amitriptyline poisoning [11,12]. Numerous human case reports and case series have since shown favorable outcomes although ECMO has been primarily used in poisonings involving pharmaceuticals such as antidysrhythmics and other cardiovascular medications, as well as tricyclic antidepressants [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that an ECMO-based management protocol significantly improves survival without severe disability, if compared with conventional mechanical ventilation. The absolute risk reduction for the primary outcome (death or severe disability) was 16 %, which translates to a number needed to treat of six patients [8]. First case report of using prolonged bypass for TRALI treatment was described by Nouraei et al in 2003 [9].…”
Section: Discussionmentioning
confidence: 99%
“…1 The dramatic increase in the use of ECLS starts with the rise of H1N1 viral pneumonia causing severe ARDS and respiratory failure. 2 Over a 3-month period from June 2009 to August 2009, 722 patients with H1N1 were treated at intensive care units in Australia and New Zealand, with 456 patients requiring mechanical ventilation. 3 Of these, 61 patients with confirmed influenza pneumonia were managed using ECLS for a median of 10 days with a 78% survival.…”
Section: Update On Epidemiologymentioning
confidence: 99%